The Development of Entrepreneurship from the Prophetic Era to the Modern Age - Sugiharto S; Naura Salsabila; Dimas Candra Alfarizi; Ayu Ainunnisa; Fachrul Aldien Kamali; Mahdania Putri; Dinda Amalia (Madani: Jurnal Ilmiah Multidisiplin, 2026)
The history of Islamic entrepreneurship demonstrates a dynamic evolution from the Prophetic era to the modern and post-modern periods. During the time of Prophet Muhammad (PBUH), business practices emphasized honesty, trustworthiness, and fairness, which became the foundation of Islamic economics. The era of the Rightly Guided Caliphs and the Umayyad dynasty expanded trade routes and established fair economic regulations. Under the Abbasid dynasty, entrepreneurship flourished with financial innovations, industrial growth, and global trade networks. The medieval period reinforced the integration of Sharia values into business activities, while colonialism imposed monopolies and economic restrictions. In the modern and post modern eras, Islamic entrepreneurship adapts to globalization, digital technology, and the halal industry while upholding Sharia principles. This historical trajectory highlights that Islamic entrepreneurship is not solely profit-oriented but also rooted in spirituality, social justice, and sustainability.